Comparative study on combustion and emission characteristics of methanol/hydrogen, ethanol/hydrogen and methane/hydrogen blends in high compression ratio SI engine. (1st May 2020) - Zhen, Xudong; Li, Xiaoyan; Wang, Yang; Liu, Daming; Tian, Zhi
Highlights: The performance of high octane fuels on high compression ratio engine is studied. Performance of hydrogen added to methanol, ethanol and methane are studied. Compare three fuel blends, the engine power and BSFC of methanol/hydrogen blend is better. The HC and NOx emissions of the methanol/hydrogen are higher. The CO emission of methane/hydrogen is lower. Abstract: Currently, alternative energy sources such as hydrogen and alcohol are increasingly used in IC engines. There is a gap in the literature of both experimental and numerical studies considering hydrogen addition in a high compression ratio engine (using methanol/hydrogen, ethanol/hydrogen and methane/hydrogen blends). Therefore, in this study, the combustion and emission performance analysis of methanol, ethanol and methane with different hydrogen volume ratios were carried out. The results showed that as the hydrogen addition, the ignition delay and the combustion duration were extended. Under the same ratio of hydrogenation, the ignition delay and combustion duration of methane/hydrogen are longer than methanol/hydrogen and ethanol/hydrogen blends. As the hydrogen ratio increases, the HC and NOx emissions of the methanol/hydrogen, ethanol/hydrogen and methane/hydrogen are increased, and the CO and CO2 emissions are decreased. Under the same ratio of hydrogenation, the engine power and BSFC of methanol/hydrogen blend is better than ethanol/hydrogen and methane/hydrogen blends, the HC and NOx emissions of the methanol/hydrogen are higher than the ethanol/hydrogen and methane/hydrogen blends, The CO emissions of methanol/hydrogen and methane/hydrogen blends are lower than the ethanol/hydrogen blends.